THE CONTRIBUTION OF PEGADAIAN ULTRA MICRO FINANCING TO MICRO-ENTERPRISE DEVELOPMENT IN SEDANAU VILLAGE FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Muhammad Ali; Nurdian Setiawan; Kartubi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the contribution of Pegadaian Ultra Micro (UMi) Financing to micro-enterprise development in Sedanau Village from the perspective of Islamic Economics. This research employs a qualitative approach with a field research design. Data were collected through observation, semi-structured interviews, and documentation involving one Pegadaian Unit Sedanau employee and four micro-enterprise customers, selected through purposive sampling. Data analysis followed the interactive model of condensation, display, and conclusion drawing, with validity ensured through source and technique triangulation. Findings show that UMi Financing contributed to micro-enterprise development across five dimensions: strengthening working capital, sustaining operational continuity, expanding product variety, maintaining business survival, and supporting household welfare. However, its contribution remains suboptimal due to the mixing of business and household finances, unstable income, and weak financial record-keeping. Assessed through Islamic Economics, the financing partially reflects the principles of justice, amanah, transparency, ta'awun, and maslahah, but requires institutional reinforcement through business mentoring and Islamic financial literacy development. Addressing these gaps will strengthen the financing program's alignment with SDG 1, SDG 8, and SDG 10 by reducing financial vulnerability, fostering productive economic activity, and narrowing structural inequality in access to finance among island-based micro-enterprise communities.